From empathy to denial : Arab responses to the Holocaust - Liṭvaḳ, Meʾir 1958- (Columbia University Press, 2009)
Reluctantly involved "bystanders," 1945/48 -- The reparations agreement between Germany and Israel, 1951/53 -- The Eichmann Affair, May 1960/May 1962 -- Arab views on the Catholic Church and the Holocaust -- Denial of the Holocaust -- The unfinished job / justification of the Holocaust -- The equation of Zionism with Nazism -- The alleged Nazi/Zionist cooperation -- Arab retrospective perceptions of Nazi Germany -- The Palestinian catastrophe (Nakba) versus the Holocaust 313 -- Breaking taboos: the new Arab discourse on the Holocaust